Factors that influence the housing preference of first time home buyers: A case study in Kota Bharu / Mohd Kamal Farid Sulaiman - Sulaiman, Mohd Kamal Farid (2011)
There are numerous factors that influence the housing preference of the first time home buyers when they considering purchasing a first home. These factors are constantly changing and difficult to measure, and often considered to be a complex bundle of attributes. This study then was conducted to identify which factor that most influence the first time home buyer’s preferences in Kota Bharu. Some of the first time home buyers also can’t determine which attributes that influence their housing preferences since they do not have an experience in housing purchase. This study will help the first time home buyer themselves to identify which factor that most influence them and also to other people such as the housing developers and the real estate agents. The research in this study is based on questionnaire distributed to the 228 respondents who were actively seeking to purchase a home for the first time in Kota Bharu. From the data analysis, it shown that all the variables used in the study which are housing attributes, neighbourhood attributes and accessibility attributes have significant relationship with the housing preferences of the first time home buyer in Kota Bharu. The findings in this study show that the most influence factor for the first time home buyers in Kota Bharu was the housing attributes and then followed by neighbourhood attributes and accessibility attributes. The finding also revealed that the variable component used under housing attributes that is house type is the most important factor among other items used in this research. This indicates that most of the respondents agreed that housing attributes is important for the selection of the first home that they want to purchase